2019
DOI: 10.1590/0074-02760190350
|View full text |Cite
|
Sign up to set email alerts
|

Iron intake is positively associated with viral load in antiretroviral naïve Brazilian men living with HIV

Abstract: BACKGROUND Iron homeostasis contribute for the human immunodeficiency virus (HIV) pathogenesis. OBJECTIVES We assessed the iron intake pattern in antiretroviral naïve Brazilian men living with HIV correlating with clinical and nutritional parameters. METHODSThe iron consumption mean was estimated according to a food frequency questionnaire (FFQ), and a 3-day food record (3dFR) submitted to the patients. HIV viral load, CD4 + T cell counts, serum iron, haematological and anthropometrics parameters were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…So far, many studies have been conducted on the effect of iron levels on the onset of symptoms and treatment of viral diseases, HBV, HCV, and HIV [13]. For example, it has been reported that high levels of iron reduce the viability of HIV-infected cells [14], and the progression of HCV infection is inhibited by the administration of exogenous iron [15,16]. Moreover, several studies have reported that serum iron levels are decreased in patients with COVID-19 [17].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many studies have been conducted on the effect of iron levels on the onset of symptoms and treatment of viral diseases, HBV, HCV, and HIV [13]. For example, it has been reported that high levels of iron reduce the viability of HIV-infected cells [14], and the progression of HCV infection is inhibited by the administration of exogenous iron [15,16]. Moreover, several studies have reported that serum iron levels are decreased in patients with COVID-19 [17].…”
Section: Introductionmentioning
confidence: 99%
“…As stated above the binding of S protein with ACE2 receptors is facilitated by TMPRSS2, a member of the type II trans-membrane serine protease (TTSP). The expression of another member of the TTSP family, namely TMPRSS6, regulates iron homeostasis via cleaving and suppressing the activity of hepcidin, [33][34][35][36]. It would be very interesting to investigate possible impact of TMPRSS2 on iron homeostasis.…”
Section: Sars-cov-2 -Iron Acquisitionmentioning
confidence: 99%